1996
DOI: 10.1093/hmg/5.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Testis-Specific cDNA on Chromosome 17q from a Region Adjacent to the Breakpoint of t(12, 17) Observed in a Patient with Acampomelic Campomelic Dysplasia and Sex Reversal

Abstract: Campomelic dysplasia (CMPD), a rare congenital disorder, is characterized by a variety of skeletal anomalies, low-set ears and, in nearly half of genotypical-male patients, sex reversal. Observations of chromosomal translocations involving chromosome 17q24-q25 in several CMPD patients have implied that disruption of one or more genes in the breakpoint region is responsible for this disease. Using fluorescence in situ hybridization, we mapped the chromosome-17 breakpoint in a patient with acampomelic CMPD and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…While a clear genotypephenotype correlation could not be established to date, the acampomelic form appears to be mild by comparison. Of 11 ACD cases in the literature in whom SOX9 mutations were reported, five carry missense mutations (Friedrich, et al, 2000;Michel-Calemard, et al, 2004;Moog, et al, 2001;Sock, et al, 2003; while the other six carry deletions or rearrangements directly affecting a cis-acting element upstream of the SOX9 coding region but not the coding region itself (Hill-Harfe, et al, 2005;Lecointre, et al, 2009;Leipoldt, et al, 2007;Ninomiya, et al, 1996;Velagaleti, et al, 2005). Of 8 cases with ACD and a XY karyotype, 4 cases (1 balanced translocation with a breakpoint upstream from the coding region, 3 missense mutations) do not show sex reversal.…”
Section: Introductionmentioning
confidence: 99%
“…While a clear genotypephenotype correlation could not be established to date, the acampomelic form appears to be mild by comparison. Of 11 ACD cases in the literature in whom SOX9 mutations were reported, five carry missense mutations (Friedrich, et al, 2000;Michel-Calemard, et al, 2004;Moog, et al, 2001;Sock, et al, 2003; while the other six carry deletions or rearrangements directly affecting a cis-acting element upstream of the SOX9 coding region but not the coding region itself (Hill-Harfe, et al, 2005;Lecointre, et al, 2009;Leipoldt, et al, 2007;Ninomiya, et al, 1996;Velagaleti, et al, 2005). Of 8 cases with ACD and a XY karyotype, 4 cases (1 balanced translocation with a breakpoint upstream from the coding region, 3 missense mutations) do not show sex reversal.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent discoveries have added several new types of RNAs to this list, including microRNA (miRNA, putative translational regulatory gene family), small interfering RNA (siRNA), and small nucleolar RNA (snoRNA, involved in rRNA modification). Among this growing list of ncRNAs is a group associated with human disease: DGCR5, breakpoint region in DiGeorge syndrome (Sutherland et al 1996); KkvLQTA-AS, implicated in Beckwith-Wiedeman syndrome (Lee et al 1999); SCA8, spinocerebellar ataxia type 8 (Nemes et al 2000); and CMPDassociated RNA, Campomelic dysplasia (Ninomiya et al 1996). As the number of non-mRNA functional RNAs increases, there is likely to be more acceptance that such RNAs may play important regulatory roles with their alterations resulting in human diseases.…”
mentioning
confidence: 99%
“…27 In campomelic dysplasia, all studied translocation breakpoints have so far been mapped at considerable distances (up to at least 300 kb) from the target gene SOX9. [23][24][25][26] An interesting point is that the clinical features of campomelic dysplasia in most of these translocation cases are less severe than observed for intragenic SOX9 mutations. With regard to the present study, this could have implications for the 1;9-translocation patient who only showed a few of the features of NPS1.…”
Section: Discussionmentioning
confidence: 99%
“…The tentative assumption is that one or At present, we can only speculate about the possible involvement of position effects in NPS1. The likely involvement of position effects has been shown to be associated with a growing number of balanced translocations associated with congenital disorders, including aniridia, 19,20 X-linked deafness, 21 holoprosencephaly 22 and campomelic dysplasia [23][24][25][26] with the common theme that dosage-sensitive transcription factors are involved. 27 In campomelic dysplasia, all studied translocation breakpoints have so far been mapped at considerable distances (up to at least 300 kb) from the target gene SOX9.…”
Section: Discussionmentioning
confidence: 99%